Mechanical Injury of Thoracic Aorta by Elephant Trunk Graft Limb following Frozen Elephant Trunk Procedure - Nair, Jayakumar Thanathu Krishnan; Sathanantham, Dinesh Kumar; Chooraiyil, Nidheesh; Nair, Vinitha V.; Jose, Jeevan J. (AORTA, 2024)
The frozen elephant trunk (FET) has been a mainstay in the treatment of acute as well as chronic aortic dissections. Although various complications have been reported in the literature, rupture of the descending thoracic aorta by the endovascular graft has, to our knowledge, not been published. We report an FET procedure following previous valve-sparing root replacement for Type A aortic dissection leading to rupture of the descending thoracic aorta.
Keywords: FET; aortic rupture; elephant trunk; hemorrhagic shock